Mechanical paramaters of sprint in female soccer players at different skill levels - Krawczyk, M.; Maciejczyk, M.; Pociecha, M.; Ozimek, M.; Markowicz, P.; Walaszek, P.; Trytek, K. (Journal of Kinesiology and Exercise Sciences, 2022)
Aim: The purpose of the present study was to evaluate the relationships between sprint mechanical parameters and sprint performance among female soccer players at different skill levels. The second objective was to assess a potential differences in force-velocity profiles between players from higher and lower sport skill level. Materials and methods: Sixty-six female soccer players (age = 23.1 ± 5.1 years) performed a 30-m sprint to assess sprint performance and mechanical variables. Speed was measured by radar technology for 5, 10, 20, and 30 m and was used to calculate the theoretical maximal velocity (V0), theoretical maximal horizontal force (F0), maximal horizontal power (Pmax), decrease in the ratio of horizontal to resultant force (DRF), and peak ratio of horizontal to resultant force (RFpeak). Results: Different force-velocity (F-V) profile parameters are determinants of sprint performance at various distances. RFpeak (r =-0.99), Pmax (r = -0.93), and F0 (r = 0.92) had the strongest associations with sprint performance at shorter (5-m) distances, while at longer (20-m) distances, V0 (r = -0.73), Pmax (r = -0.94), and RFpeak (r = -0.88) were largely associated with sprint performance. The players from higher sports skill level showed higher levels of F0, RFpeak, Pmax and time to 10 meter distance. Conclusion: The results of this study suggest that depending on sprint distance used for testing and training procedures in female soccer players, the most informative parameters are Pmax, RFpeak, F0, and V0. As the skill level in female soccer players increases, an increase in maximal theoretical horizontal force during sprinting can be observed.